Landing page optimization the definitive guide to testing and tuning for conversions, second edition - Ash, Tim 1965-; Page, Rich; Ginty, Maura (John Wiley & Sons, 2012)
Annotation
Keywords: Web sites -- Evaluation; Web sites -- Testing; Web sites -- Design; Internet marketing; Sites Web; Évaluation; Sites Web; Conception; Marketing sur Internet; COMPUTERS; Digital Media; General; COMPUTERS; Interactive & Multimedia; COMPUTERS; Web; Site Design; COMPUTERS; Web; User Generated Content; Web sites; Design; Web sites; Evaluation; Website